Comparison of Biometry Measurements Using Standard Partial Coherence Interferometry versus New Scheimpflug Tomography with Integrated Axial Length Capability - Haddad, Jorge Selem (Clin Ophthalmol, 2020)
PURPOSE: To compare biometry measurements obtained by a partial interferometer biometer (IOLMaster 500) to the new Scheimpflug tomography with an integrated axial length biometer module (Pentacam AXL). PATIENTS AND METHODS: Cataract patients who underwent biometric measurements with the IOL Master 500 and the Pentacam AXL from July to November 2017 were enrolled in this study. Comparisons were performed for axial length (AL), keratometry (K), and anterior chamber depth (ACD). The Pearson correlation coefficient and the 95% limits of agreement (LoA) were calculated. Paired Student’s t-tests and Bland-Altman plots were used to assess the differences between devices. RESULTS: One hundred and sixty-six eyes of 92 patients were analyzed. There were no statistically significant differences in AL (p=0.558) or flat K (p=0.196) values between the IOL Master 500 and Pentacam AXL measurements. Statistically significant differences were found between the two devices with respect to steep K, ACD, and mean K measurements (p<0.001). CONCLUSION: Both devices provided similar measurements of AL and flat K, though there were statistically significant differences in ACD, steep K, and mean K measurements.